Do justice perceptions support the concept of equal sacrifice? Evidence from Germany - Maria Metzing (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The ability-to-pay approach assesses taxes paid as a sacrifice by the taxpayers. This raises the question of how to define and how to measure it: in absolute, relative, or marginal terms? U.S. respondents prefer a tax schedule that is either a pure (absolute) Equal Sacrifice or a mixture of Equal Sacrifice and Utilitarianism [Weinzierl, 2014]. To determine whether Germans prefer absolute, relative, or marginal Equal Sacrifice principle for their income taxation, I use a question item from the German Socio-Economic Panel (SOEP) to obtain information on the level of taxes individuals consider as fair. I estimate tax and transfer schedules with regard to three Equal Sacrifice definitions and analyze which one of the three best fits the data. The absolute and the relative Equal Sacrifice principle are the dominant candidates in terms of statistical fit.
Keywords: H21; D63; 330; Equal Sacrifice; Optimal Taxation; Fair Taxation